2013
DOI: 10.1074/jbc.m113.464578
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Paralogous Thiol-disulfide Oxidoreductases in Streptococcus gordonii

Abstract: Background: Thiol-disulfide oxidoreductases catalyze disulfide bond formation in extracellular proteins. Results: A new oxidoreductase, SdbA, affects multiple phenotypes in Streptococcus gordonii and is required for production of disulfide-bonded proteins. Conclusion: SdbA is a new type of oxidoreductase that has important biological functions. Significance: This is the first indication that thiol-disulfide oxidoreductases are important to the physiology of Firmicute bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…Further analysis is needed to elucidate the role of SaDsbA in vivo. Finally, a single DsbA-like factor has also been identified in S. gordonii (67). Similar to B. subtilis and S. aureus, this putative oxidoreductase has been implicated in competence development.…”
Section: Gram-positive Disulfide-bond-forming Pathwaysmentioning
confidence: 91%
See 1 more Smart Citation
“…Further analysis is needed to elucidate the role of SaDsbA in vivo. Finally, a single DsbA-like factor has also been identified in S. gordonii (67). Similar to B. subtilis and S. aureus, this putative oxidoreductase has been implicated in competence development.…”
Section: Gram-positive Disulfide-bond-forming Pathwaysmentioning
confidence: 91%
“…DsbA-like genes have also been identified in Staphylococcus aureus and Streptococcus gordonii (66,67). S. aureus DsbA (SaDsbA) is a membrane-bound lipoprotein that was shown in vitro to have thiol-disulfide oxidoreductase activity (68).…”
Section: Gram-positive Disulfide-bond-forming Pathwaysmentioning
confidence: 99%
“…Previously, we found that ⌬sdbA mutants were defective in bacteriocin activity (26). To investigate how SdbA affects bacteriocin production, we started by constructing a catalytically inactive SdbA active site mutant, to determine whether bacteriocin production requires the oxidoreductase activity of SdbA.…”
Section: Resultsmentioning
confidence: 99%
“…S. gordonii SecCR1 is a derivative of S. gordonii DL-1 Challis that secretes a single-chain variablefragment antibody (scFv) against complement receptor 1 (CR1), which is a protein that requires disulfide bonds for stability (30). This strain was used in our previous studies of disulfide bond formation in S. gordonii (26), and the S. gordonii SecCR1 ⌬sdbA mutant has the same phenotype as the ⌬sdbA mutant of S. gordonii DL-1 Challis (see Fig. S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation